2018
DOI: 10.1891/0886-6708.33.6.983
|View full text |Cite
|
Sign up to set email alerts
|

Cyber Partner Abuse: A Systematic Review

Abstract: With recent technological advances, cyber partner abuse has become increasingly problematic. The purpose of this study was to systematically review the existing literature on cyber partner abuse. This systematic review examines the characteristics and conceptualizations in the cyber partner abuse literature as well as the major topics the research has explored. Literature searches used keywords related to cyber partner abuse. In total, 37 articles were included in this review. Inductive qualitative content ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 56 publications
5
55
0
Order By: Relevance
“…Our results were also contrary to what has been found with regard to offline DV: parental and family variables are key risk factors of physical and psychological DV perpetration and victimization (cf. Taylor & Xia, 2018). Gracia-Leiva et al (2019), in their metaanalysis on DV, found that the social and community environment was more closely related to DV as opposed to individual factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results were also contrary to what has been found with regard to offline DV: parental and family variables are key risk factors of physical and psychological DV perpetration and victimization (cf. Taylor & Xia, 2018). Gracia-Leiva et al (2019), in their metaanalysis on DV, found that the social and community environment was more closely related to DV as opposed to individual factors.…”
Section: Discussionmentioning
confidence: 99%
“…In Deans and Bhogal's (2017) study, gender was significantly associated with CDA, with women reporting less perpetration of CDA than men, contrary to other previous studies (e.g., Bennett et al, 2011;Burke et al, 2011) were women were more likely than men to perpetrate controlling online behaviors. These inconsistent findings have been attributed to the fact that men and women perpetrated CDA differently: men tend to perpetrate more direct acts of aggression (Perry & Pauletti 2011;Taylor & Xia, 2018) while women more indirect acts (Hyde, 2005), such as monitoring behaviors (Taylor & Xia, 2018). Studies (e.g., Sánchez et al, 2015;Smith et al, 2018) examining the relation between age and CDA victimization have also reached discrepant results: Smith et al (2018) concluded that age was not associated with cyber victimization, cyber perpetration, or mutual cyber violence; in turn, Sánchez et al (2015) reveled a positive association between age and CDA victimization, although the size of these associations varied according to the different abusive typologies.…”
Section: Risk and Protective Factors Of Cyber Dating Abusementioning
confidence: 99%
See 1 more Smart Citation
“…In line with former research, ICT like smartphones (text messages, messenger services), websites of social networks (Facebook, Twitter), and telephone applications (Instagram, Snapchat), facilitate constant communication between partners [4], but can also be used as a means to directly exercise aggression and to control partners or former partners [5]. Although various terms can be used to name this phenomenon, such as "electronic dating violence" [6], "digital forms of dating violence" [7], "intimate partner cyber harassment" [8], "cyber partner abuse" [9], "cyber psychological abuse" [10], the term most widely used by the scientific community is "cyber dating abuse" [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Cyber dating abuse includes direct aggression conducts that intend to deliberately harm one's partner (e.g., sharing private information and posting it on technological platforms, and insulting or threatening using these platforms), but also includes control behaviors that invade people's privacy or are related to monitoring someone (e.g., controlling access to social networks or using one's partner's password without his/her permission) [9]. These strategies often work as a power and control mechanism within relations, and are frequently motivated by jealousy and mistrust [13].…”
Section: Introductionmentioning
confidence: 99%